1997
DOI: 10.1002/zaac.19976230199
|View full text |Cite
|
Sign up to set email alerts
|

Crystal, molecular, and electronic structure of Trans‐bis[ethanone, 1‐(2‐hydroxyphenyl)‐oximato]Nickel(II)

Abstract: The compound [Ni(apo~)~], (where apoxdenotes the anion of 2-hydroxyacetophenoneoxime, C8H8N02-), was prepared and studied by means of spectroscopic (IR, 'H NMR, UV-Vis) measurements and theoretical calculations employing the Hiickel method. The structure was determined by X-ray diffraction studies. The unit cell is monoclinic (space group P21/c)0 with dimensions a = 7.845(1), Keywords: 2-Hydroxyacetophenoneoxime complex; nickel b = 9.911(2), c = 19.371(2) A, ,b'= 94.37(1)" and contains four formula units. Hiic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Each Ni atom is surrounded by two nitrogen and two oxygen atoms at distances 1.887(2) Â and 1.823(2) À respectively, in a nearly centrosymmetric distorted square-planar arrangement. The fused rings, one chelate and the other cyclic lie in this plane and so for the hydrogens that form quite strong hydrogen bonds [02*-01 2.47 Â (comparable with one of the two respective distances in [4], 02*-H-01 1.7288 À, 0(2)*-H2-0(l) 135.8° and 0 (2) (7) 0.0648 (9) 0.0371 (7) 0.0150 ( …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Each Ni atom is surrounded by two nitrogen and two oxygen atoms at distances 1.887(2) Â and 1.823(2) À respectively, in a nearly centrosymmetric distorted square-planar arrangement. The fused rings, one chelate and the other cyclic lie in this plane and so for the hydrogens that form quite strong hydrogen bonds [02*-01 2.47 Â (comparable with one of the two respective distances in [4], 02*-H-01 1.7288 À, 0(2)*-H2-0(l) 135.8° and 0 (2) (7) 0.0648 (9) 0.0371 (7) 0.0150 ( …”
Section: Discussionmentioning
confidence: 98%
“…This conformation explains the strong tension of the crystal to split vertically to this direction. The conformation molecule is trans planar, similar to that of bis(propanone-1 -[2-hydroxyphenyl]oximato)Pd(II) and of bis[ethanone-l-[2-hydroxyphenyl]oximato)Ni(II) structures[4,5].…”
mentioning
confidence: 95%
“…For general background to the applications of 2-hydroxyaryloxime complexes in extractive metallurgy and biology, see: Keeney et al (1984); Elo & Lumme (1985); Chaudhuri (2003); Milios et al (2007). For related structures, see: Hatzidimitriou et al (1997); Voutsas et al (1999).…”
Section: Related Literaturementioning
confidence: 99%
“…E65, m1305 [https://doi.org/10.1107/S1600536809039257] (Chaudhuri, 2003;Elo & Lumme, 1985;Keeney et al, 1984;Milios et al, 2007). (Hatzidimitriou et al, 1997), and bis[2-(5-methyl-1-(hydroxyimino)ethyl)phenolato]nickel (Voutsas et al, 1999), have been reported. As a continuation of these studies, the structure of the title complex, (I), is described herein.…”
Section: Supporting Informationmentioning
confidence: 99%
“…In the title compound, which is isostructural with the corresponding nickel(II) (Hatzidimitriou et al, 1997) and copper(II) (Zhou et al, 1985) complexes, the geometry of the cobalt(II) ion is best described as distorted square-planar. The Co-N bond lengths of 1.889 (3) and 1.892 (3) Å are in agreement with the corresponding distances found in other four-coordinated Co complexes (Fachinetti et al, 1979;Rudolf et al, 1988).…”
mentioning
confidence: 99%